Aspek Hukum Dalam Perjanjian Kerja Bersama - D, Daud (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The purpose of this study is to determine how the implementation of the work agreement between the Employee Union and Management and what obstacles are in the PKB and what efforts are made to overcome obstacles to implementation. The research method used in this study is the normative legal research method and it can be concluded that: 1. The implementation of the Collective Labor Agreement (PKB) between Workers and Company Management starting from the first PKB to the last PKB to be valid, there are not many violations in terms of the quantity of problems. However, violations of the PKB also result in obstacles to the working relationship between employees. 2. Implementation, how to make a joint agreement, the role and function of the Collective Labor Agreement (PKB) must still be considered in determining policies or decisions concerning the existence of the workforce. Because with Sekar's involvement from the start in determining policies concerning employees through Sekar's role and function, it can prevent industrial relations disputes.